Treatment of alcohol use disorder in patients with liver disease. (February 2022) - Nielsen, Anette Søgaard; Askgaard, Gro; Thiele, Maja
Abstract: Alcohol contributes to more than 5% of global mortality, and causes more than half of all liver-related deaths. The Alcohol Use Disorders Identification Test (AUDIT) can be used to detect those patients with hazardous drinking and alcohol dependence who will benefit from psychosocial and pharmacological alcohol treatment. Psychosocial treatments range from brief interventions and cognitive behavioral therapy, to experimental neuropsychological treatments. Psychosocial intervention can be combined with acamprosate or naltrexone as first line pharmacological treatments. For patients with liver disease, abstinence increases survival and is therefore an important treatment goal. Acamprosate is a good choice, as it prevents relapse to drinking with a number needed to treat of 12. There are no reports indicating high risks of liver toxicity for acamprosate or naltrexone, but evidence is scarce. We recommend vigorous screening for alcohol use disorder in liver disease patients, followed by psychosocial intervention and complemented by pharmaceutical therapy.